Strategia ponadlokalna jako nowy instrument planowania rozwoju społeczno-gospodarczego .......... 97 - Łysoń, Artur (Samorząd terytorialny na Dolnym Śląsku: Sprawy, dylematy i wyzwania, 2025)
THE SUPRA-LOCAL DEVELOPMENT STRATEGY AS A NEW INSTRUMENT OF SOCIO-ECONOMIC DEVELOPMENT PLANNINGSocio-economic development planning in Poland may be described as a continuously evolving system undergoing frequent reforms. One of the most recent innovations is the introduction of the supra-local development strategy. Its main objective is to foster joint action among local and supra-local government units in response to contemporary development challenges. After several years of implementation since late 2020, it is now possible to undertake a preliminary assessment of this instrument.